Analisis Sistem Instalasi Kelistrikan pada Swiss-Belhotel Makassar dengan Menggunakan Program ETAP - Ishak Amar; Imam Ridwan Tanaka; Riyki Apriandi; Usman Haya (Universitas Wahid Hasyim, 2025)
Swiss-Belhotel Makassar as a five-star hotel requires a reliable electrical installation system to support operations and customer comfort. Electrical system evaluation is important to ensure that system performance remains optimal, safe, and meets standards. This study aims to analyze and evaluate the existing condition of the electrical installation at Swiss-Belhotel Makassar using the Electrical Transient Analyzer Program (ETAP) software. The methods used include primary and secondary data collection, single line diagram system modeling, and short circuit current simulation and load analysis. The evaluation results show that there are several system components that are approaching their maximum capacity limits, as well as load imbalances between phases that need to be corrected to avoid potential disruptions and low energy efficiency. By using ETAP simulation, technical recommendations are prepared such as protection adjustments, load balancing, and system configuration improvements. This evaluation provides an important overview in efforts to improve the reliability and safety of the hotel's electrical system as a whole.